Reinforced Polymers for Electroactive Devices - Gaur A.; Maiti P. (My University, 2025)
In this chapter, different electroactive polymers (EAPs) and reinforced polymer composites for device applications were discussed. Electroactive devices are widely used in all areas today. Electroactive devices show changes in shape and size when exposed to an electric field or give an electrical output signal when subjected to an external force. Their most common applications are in actuators and sensors. Previously, only ceramic materials were used to manufacture sensors and actuators. Ceramic materials can withstand a great force, but only a few can be deformed. In contrast, polymers can be greatly deformed at the same voltage, since the toughness and elongation at break of polymers are much higher than ceramics. Biocompatible polymers can also be used in the biomedical field. Some specific advantages of polymers are also discussed as electroactive material. These devices can be made of pure EAPs or filled polymers, especially with nanofiller geometry. Some nanofillers are piezo- or ferro-electric, and their inclusion into the polymers, in general, increases the electroactive properties of polymer composites. On the other hand, some nanofillers, such as nanoclay, can induce the electroactive phase in the polymer, even though the components are not intrinsically electroactive. A detailed discussion on the different nanofillers for making reinforced polymer composites for device applications was presented in this manuscript. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2020.